ANALYSING THE PREDICTIVE EFFECTS OF GENDER, PROCEDURAL JUSTICE AND DISTRIBUTIVE JUSTICE ON ORGANIZATIONAL COMMITMENT AMONG FIRE SERVICE PERSONNEL IN ANAMBRA STATE - Anazor, Chinenye S.; Onwuamaegbu, Promise O. (African Journal of Social and Behavioural Sciences, 2024)
The study investigated the predictive effects of gender, procedural justice and distributive justice on organizational commitment of fire service workers in Anambra State. A total of 119 participants comprising 74 males and 45 females with ages ranging from 29 to 51 years (Mean = 39.50, standard deviation = 4.20) were selected from six fire service stations in Anambra State through convenience sampling technique. The study was guided by three hypotheses. Data collection relied on Two instruments: the Organizational Justice Scale (OJC) developed by Niehoff and Moorman (1993) and the Organizational Commitment Questionnaire developed by Buchanan (1974). The research design employed was cross-sectional survey design and data analysis was conducted using hierarchical multiple regression. The finding of the study confirmed that gender, procedural justice and distributive justice separately predicted organizational commitment among fire service personnel in Anambra State. The study recommends that the government and managers should prioritize fairness in treatment and rewards, while efforts from government bodies and company owners should aim to enhance organizational commitment. Additionally, gender should not influence employment decisions; adopting a merit-based approach promotes inclusivity and equality.